Contemporary understanding of the risk factors for chronic kidney disease in cold area - Wei Xinrui; Wang Yongchen (Frigid Zone Medicine)
The management of chronic kidney disease (CKD) patients in cold areas is an important task in the daily practice of primary medical and health institutions. An important way to reduce the burden of CKD is to achieve early identification of and implement timely intervention on the relevant risk factors. Studies have shown that diet, alcohol, tobacco, air, sedentary and other factors in cold areas have negative impacts on human kidneys; yet, our current understanding of the effect of cold stimulation on CKD remains blurry. This paper introduces the research progress of risk factors related to CKD in cold areas and analytically summarizes the pathogenesis of CKD caused by cold stimulation, aiming to provide a reference work for the prevention, screening, evaluation, and management of CKD in cold areas.